Lectotypification of Indopiptadenia oudhensis (Leguminosae: Mimosoideae) - Tiwari, Arjun Prasad (Phytotaxa, 2017)
The monotypic genus Indopiptadenia Brenan (1955: 178) is represented by the species Indopiptadenia oudhensis (Brandis [1874: 168]) Brenan (1955: 178) occurring in India and the Nepal region (Bajpai et al. 2014). In India the species is distributed in the Bahraich, Gonda, and Gorakhpur districts of Uttar Pradesh and the Champawat district of the Kumaun region in Uttarakhand state, India. The species is also uncommonly found in the Dang district of Western Nepal. Indopiptadenia has been derived from Piptadenia Bentham (1840: 135) because of its unusual morphology characterised by the uni-or bijugate leaflets, eglandular petiole, glandular leaf rachis, corolla-lobes being free to their base and elongated seeds.